FAKTOR PEMBENTUK PERSEPSI RUANG KOMUNAL DI PEMUKIMAN NELAYAN (Studi Kasus: Pemukiman Nelayan Tambak Mulyo Semarang) - Satriya Wahyu Firmandhani; Bambang Setioko; Erni Setyowati (Diponegoro University, 2013)
In certain settlement, human always interact with the physical setting arround of them. That interaction causesperception inside of that human, because perception is the process of organizing and interpretating of stimulusprovided by the environment (Rita, 1983). So the perception is strongly influenced by the individual human andphysical surroundings. Based on the theory of perception, found problems in Tambak Mulyo as fishermensettlement in Semarang, where the inhabitants of Tambak Mulyo do the communal activities on the roadenvironment. Road environment should be a mode of land transport circulation is also used for the communalspace. Seeing this phenomenon, it can be concluded that there is the perception of communal space in thefishermen settlement in Tambak Mulyo. And this study aimed to explore the factors forming the perception ofcommunal space.In answering the research objectives, the research paradigm used is a quantitative rationalistic to constructfactor variables. In constructing the factor variabless, based on the theory that the perception of the individualand the setting up of the physical environment (Sarlito, 1992). So that the required variables are perceptionvariables and variables of communal space. The variables is operationalized into a questionnaire that is easy tounderstand the respondents, next after the questionnaire data collected, the data were analyzed using factoranalysis statistical test, so of many variable factors that could wake is reduced to just a few factors thatsignificantly causes the perception of communal space in the fishermen settlement.At the output of this research, revealed about the causal factors of the perception of communal space in thefishermen settlement. These factors is a collection of variable factors that have a strong correlation in theanalysis. By knowing the factors forming the perception of communal space in the fishing settlement, expected toprovide input in the planning and design of fishing settlements.Key words : Perception, Communal Space, Physical Setting